BALTICA UPSIDE DOWN: A NEW PLATE TECTONIC MODEL FOR RODINIA AND THE IAPETUS OCEAN - Hartz E.H.; Torsvik T.H. (My University, 2002)
We propose that Baltica was geographically inverted throughout the Neoproterozoic and therefore suggest reassessment of the classic Wilson Cycle paleoreconstruction de- picting an Atlantic-type early Paleozoic (Iapetus) ocean between western Norway and East Greenland. Our new reconstruction dismisses the need for 1808 rotation of Baltica after breakup of Iapetus and presents more plausible geologic correlations between Baltica, Laurentia, and Gondwana than those accompanying previous fits. In our reconstruction, the breakup that led to the formation of the Iapetus Ocean was initiated at a junction between a rift (Laurentia-Gondwana), a right-lateral fault (Laurentia-Baltica), and a trench (inverted Baltica-Gondwana), thereby linking the late Precambrian Iapetus opening to the Timanian and Avalonian orogenies between Gondwana and an inverted Baltica.
Keywords: Iapetus; Wilson Cycle; Precambrian; Avalonia; Rodinia; Baltica; paleomagnetism; Precambrian; Докембрий